2023
DOI: 10.3390/coatings13040794
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Incident Energy Effect on the Properties of TiN Films

Abstract: In this work, to investigate the physical vapor deposition (PVD)-deposited TiN coating on the TiN(001) substrate, the process was simulated using the molecular dynamics (MD) method with the 2NN-MEAM (nearest-neighbor modified embedded atom method) potential. The results revealed that the growth mode of TiN film is determined by incident energy. When the incident energy is low, the deposited atoms have weak mobility after momentum transfer with the substrate and cannot fill the vacancy in the TiN film, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Low incident energy reduces the mobility of atoms, and some atoms are adsorbed by the deposited atoms before reaching the substrate. As the number of deposited atoms increases, they aggregate to form larger nuclei, resulting in low nucleation density (Li et al , 2023). As the incident energy increases, the number of atoms reaching the substrate increases.…”
Section: Resultsmentioning
confidence: 99%
“…Low incident energy reduces the mobility of atoms, and some atoms are adsorbed by the deposited atoms before reaching the substrate. As the number of deposited atoms increases, they aggregate to form larger nuclei, resulting in low nucleation density (Li et al , 2023). As the incident energy increases, the number of atoms reaching the substrate increases.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, only 550 ps of system evolution were simulated, which is not enough to detect all effects at a realistic flux density. The study of film growth modes was also carried out in [61], where the influence of the energy of depositing atoms on the nature of film growth was shown. The results showed that low energies lead to the formation of "islands".…”
Section: Vn Tinmentioning
confidence: 99%